Flea-borne pathogens in the cat flea Ctenocephalides felis and their association with the mtDNA diversity of the flea hosts - Wahid, Noor Azrizal; Azirun, Mohd Sofian; Low, Van Lun (Elsevier, 2021)
Flea-borne pathogens were screened from 100 individual cat fleas using a PCR approach, of which 38 % were infected with at least one bacterium. Overall, 28 % of the flea samples were positive for Bartonella as inferred from ITS DNA region. Of these, 25 % (7/28) were identified as Bartonella clarridgeiae, 42.9 % (12/28) as Bartonella henselae consisted of two different strains, and 32.1 % (9/28) as Bartonella koehlerae, which was detected for the first time in Malaysia. Sequencing of gltA amplicons detected Rickettsia DNA in 14 % of cat flea samples, all of them identified as Rickettsia asembonensis (100 %). None of the flea samples were positive for Mycoplasma DNA in 16S rRNA gene detection. Four fleas were co-infected with Bartonella and Rickettsia DNAs. Statistical analyses reveal no significant association between bacterial infection and mtDNA diversity of the cat flea. Nevertheless, in all types of pathogen infections, infected populations demonstrated lower nucleotide and haplotype diversities compared to uninfected populations. Moreover, lower haplotype numbers were observed in infected populations.